1997
DOI: 10.1021/jm970220w
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biology of a 7-Nitro-2,1,3-benzoxadiazol-4-yl Derivative of 2-Phenylindole-3-acetamide:  A Fluorescent Probe for the Peripheral-Type Benzodiazepine Receptor

Abstract: Benzodiazepines are among the most highly prescribed drugs due to their pharmacological action of relieving anxiety mediated through modulating the activity of γ-aminobutyric acid receptors in the central nervous system. 1 The peripheral-type benzodiazepine receptor (PBR) is another class of binding sites for benzodiazepines distinct from the aforementioned neurotransmitter receptors. The PBR was originally discovered because it binds the benzodiazepine diazepam with relatively high affinity. 2 Further studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
0
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 35 publications
4
47
0
2
Order By: Relevance
“…Incubation of Leydig cells with a combination of LH (0.1 ng/ml) plus FGIN-1-27 resulted in significantly higher T production than when the cells were incubated with FGIN-1-27 alone ( Figure 1G). Additionally, as is consistent with previous reports (37,38,43), Ro5-4864 and FGIN-1-27 stimulated steroid (progesterone) production by MA-10 tumor cells (not shown). In contrast to primary cells, however, the response of MA-10 cells to Ro5-4864 was greater than that to FGIN-1-27.…”
Section: In Vitro Effects Of Tspo Drug Ligands Ro5-4864 and Fgin-1-27supporting
confidence: 93%
See 1 more Smart Citation
“…Incubation of Leydig cells with a combination of LH (0.1 ng/ml) plus FGIN-1-27 resulted in significantly higher T production than when the cells were incubated with FGIN-1-27 alone ( Figure 1G). Additionally, as is consistent with previous reports (37,38,43), Ro5-4864 and FGIN-1-27 stimulated steroid (progesterone) production by MA-10 tumor cells (not shown). In contrast to primary cells, however, the response of MA-10 cells to Ro5-4864 was greater than that to FGIN-1-27.…”
Section: In Vitro Effects Of Tspo Drug Ligands Ro5-4864 and Fgin-1-27supporting
confidence: 93%
“…To address this hypothesis, we determined the in vitro effects of the selective, high-affinity TSPO drug ligands N,N-dihexyl-2-(4-fluorophenyl) indole-3-acetamide (FGIN-1-27) and benzodiazepine 4Ј-chlorodiazepam (Ro5-4864) (37,38) on steroidogenesis by primary Leydig cells isolated from the testes of aged (21 months old) in comparison with young adult (3 months old) Brown Norway rats and the in vivo effects of administered FGIN-1-27 on serum T levels in young and old animals. We show that young and aged cells stimulated with TSPO drug ligand produced T at equivalent levels and that administering FGIN-1-27 to aged rats resulted in significantly increased serum T levels to those of young rats.…”
mentioning
confidence: 99%
“…Carayon et al showed that PBR transfection could protect Jurkat leukaemia cells from ROS induced cytotoxicity (Carayon et al, 1996). However, we have observed that SUDHL4 and BV173 cells exhibit comparable PBR expression, (measured using 7-nitro-2,1,3-benzoxadiazol-4-y1 derivative of 2-phenylindole-3-acetamide (NBD FGIN-1-27 analogue), a fluorescent PBR probe (Kozikowski et al, 1997)), yet exhibit differential tolerance to the effects of PK11195 on ∆Ψ m ; furthermore, Jurkat T cells which lack demonstrable NBD FGIN-1-27 binding, dramatically produce ROS in response to PK11195 (unpublished data). The origin of PK11195 induced ROS is unknown.…”
Section: Discussionmentioning
confidence: 97%
“…To directly image the PBR and to study the specificity of the PBR ligand PK11195 for the Reh cell line, a specific fluorescent probe for the PBR, FGIN-1-27 (Alexis Biochemicals, San Diego, CA; ref. 16), was used. Cells were incubated with FGIN-1-27 (0.5 Amol/L) for 45 minutes in the absence and presence of PK11195 (200 Amol/L; Sigma) to determine if PK11195 could inhibit binding of the fluorescent probe to PBR.…”
Section: Methodsmentioning
confidence: 99%